2006
DOI: 10.1177/0886260505282564
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Long-Term Psychosocial Functioning in a National Sample of American Women

Abstract: Using a nationally representative sample of American married or cohabiting women, this prospective study examined women who reported or denied intimate partner violence (IPV) at wave 1 and compared them on a range of psychosocial outcomes at a 5-year follow-up. This study also examined the rate of divorce or separation during the 5-year interval among women who reported IPV at wave 1 and explored whether certain predictors were related to ending an abusive relationship with an intimate partner during the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
234
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(249 citation statements)
references
References 21 publications
9
234
3
3
Order By: Relevance
“…Likewise, the proposition that reduced maternal selfconfidence and self-esteem is sometimes in the path between SPVP and EBF seems quite tenable. This hypothesis is strengthened by connecting previous findings pointing out that low confidence and feelings of worthlessness are consistent with the long-term psychological consequences of SPVP victimization (38,39) , and with other studies indicating that the psychosocial wellbeing of women during pregnancy is an important protective factor for early weaning (5,(40)(41)(42)(43)(44)(45)(46)(47) . The importance of maternal self-esteem as a mediator of the relationship between SPVP and EBF is also reasonable when comparing the gradual effects of introducing the dimensions in the multivariate model.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, the proposition that reduced maternal selfconfidence and self-esteem is sometimes in the path between SPVP and EBF seems quite tenable. This hypothesis is strengthened by connecting previous findings pointing out that low confidence and feelings of worthlessness are consistent with the long-term psychological consequences of SPVP victimization (38,39) , and with other studies indicating that the psychosocial wellbeing of women during pregnancy is an important protective factor for early weaning (5,(40)(41)(42)(43)(44)(45)(46)(47) . The importance of maternal self-esteem as a mediator of the relationship between SPVP and EBF is also reasonable when comparing the gradual effects of introducing the dimensions in the multivariate model.…”
Section: Discussionsupporting
confidence: 85%
“…*Denotes a significant difference between groups, p<0.05. Self-perceived health ranges from 1(poor) to 5 (excellent), with higher scores reflecting higher perceived health findings further highlight the importance of detecting IPV because these mental health problems are often chronic in this population, 33,34 and treatment of these symptoms may reduce women's risk for subsequent IPV. 35 Thus, detection is critical because it provides the opportunity to treat associated health problems and offer appropriate social and mental health interventions to increase safety and well-being.…”
Section: Discussionmentioning
confidence: 90%
“…Although previous research has found that those in violent intimate relationships are more likely to have depressive symptoms in the aftermath of their IPV experiences (Anderson, 2002;Prospero, 2008;Zlotnick, Johnson, & Kohn, 2006), other studies have explored whether depressive symptoms occur prior to the violent interactions (Keenan-Miller, Hammen, & Brennan, 2007). For example, Lipsky, Caetano, Field, and Bazargan (2005) found that depressive symptoms predicted both IPV perpetration and victimization.…”
Section: Depressive Symptomologymentioning
confidence: 97%